Some luck - Smiley, Jane (Smiley, Jane. Last hundred years., 2014)
"An epic novel that spans thirty years in the lives of a farm family in Iowa, telling a parallel story of the changes taking place in America from 1920 through the early 1950s"--Provided by publisher.